The recognition of Customary Marriages Act: many women still left out in the cold - Jansen, R-M. (Faculty of Law, University of the Free State, 2002)
This paper focuses on the position of women in monogamous customary marriages concluded before the commencement of The Recognition of Customary Marriages Act, 120 of 1998. This Act alleviated (on appearances) the subordination and inferior status of women in cutomary law. Sec 6 specifically stipulates that a wife in a customary marriage has, on the basis of equality with her husband and subject to the matrimonial system governing the marriage, full status and capacity. According to sec 7 the proprietary consequences of marriages entered into before the commencement of the Act continue to be governed by customary law. However, the question arises - what is the point of sec 6 granting a wife equality with her husband and the capacity to acquire assets, but still subject to the customary law which places the marital property under the control and almost complete discretion of her husband? Many of the sections of the Divorce Act and the Matrimonial Property Act (which was introduced mainly to improve the postion of women) are also only applicable to customary marriages entered into after the commencement of the Act. It is submitted that arguments which supported a retrospective change to proprietary regimes, should have been adopted in the legislation. Sec 7(1) of the Act should be amended to provide that a monogamous customary marriage entered into before the commencement of the Act, is a marriage in community of property and of profit and loss.

Hierdie artikel fokus op die posisie van vroue in monogame gebruiklike huwelike gesluit voor die inwerkingtreding van die Wet op Erkenning van Gebruiklike Huwelike, 120 van 1998. Hierdie Wet poog om die ondergeskikte en minderwaardige status wat vroue in die inheemse reg het, op te hef. Art 6 bepaal dat 'n vrou in 'n gebruiklike huwelik op grond van gelykheid met haar man en onderhewig aan die huweliksgoederebedelingwat die huwelik reël, volle status en bevoegdhede het. Volgens art 7 bly die vermoënsregtelike gevolge van 'n gebruiklike huwelik wat voor die inwerkingtreding van die Wet gesluit is, egter onderhewig aan die gewoontereg. Wat is dan die waarde van art 6, wat gelyke status met haar eggenoot en die bevoegdheid om eiendom te verkry verleen, maar dit steeds onderworpe aan die gewoontereg maak (in terme waarvan al die huweliksbates onder die eggenoot se kontrole en diskresie val?). Baie van die artikels van die Wet op Egskeidingen die Wet op Huweliksgoedere (wat hoofsaaklik ingestel is om die posisie van die vrou te verbeter) is ook slegs van toepassing op gebruiklike huwelike wat aangegaan is na die inwerkingtreding van die Wet. Dit word aan die hand gedoen dat die argumente ten gunste van 'n terugwerkende wysiging van die vermoënsregtelike bestel, in wetgewing aanvaar moes gewees het. Art 7(1) moet gewysig word en bepaal dat 'n monogame gebruiklike huwelik wat gesluit is voor die inwerkingtreding van die Wet, 'n huwelik binne gemeenskap van goed en van wins en verlies is.